The Butyrogenic and Lactic Bacteria of the Gut Microbiota Determine the Outcome of Allogenic Hematopoietic Cell Transplant - Devaux, Christian Albert; Million, Matthieu; Raoult, Didier (Frontiers in Microbiology, 2020)
Graft versus host disease (GVHD) is a post-transplant pathology in which donor-derived T cells present in the Peyer's patches target the cell-surface alloantigens of the recipient, causing host tissue damages. Therefore, the GVHD has long been only considered a purely immunological process whose prevention requires an immunosuppressive treatment. However, since the early 2010s, the impact of gut microbiote on GVHD has received increased attention. Both a surprising fall in gut microbiota diversity and a shift towards Enterobacteriaceae were described in this disease. Recently, unexpected results were reported that further link GVHD with changes in bacterial composition in the gut and disruption of intestinal epithelial tight junction leading to abnormal intestinal barrier permeability. Patients receiving allogenic hematopoietic stem cell transplant (allo-HCT) as treatment of hematologic malignancies showed a decrease of the overall diversity of the gut microbiota that affect Clostridia and Blautia spp and a predominance of lactic acid bacteria (LAB) of the Enterococcus genus, in particular the lactose auxotroph Enterococcus faecium. The reduced microbiota diversity (likely including Actinobacteria, such as Bifidobacterium adolescentis that cross feed butyrogenic bacteria), deprives the butyrogenic bacteria (such as Roseburia intestinalis or Eubacterium) of their capacity to metabolize acetate to butyrate. Indeed, administration of butyrate protects against the GVHD. Here we review the data highlighting the possible link between GVHD and lactase defect, accumulation of lactose in the gut lumen, reduction of Reg3 antimicrobial peptides, narrower enzyme equipment of bacteria that predominate post-transplant, proliferation of Enterococcus faecium that use lactose as metabolic fuels, induction of innate and adaptive immune response against these bacteria which maintains an inflammatory process, elevated expression of myosin light chain kinase 210 (MLCK210) and subsequent disruption of intestinal barrier, translocation of microbial products (lactate) or transmigration of LAB within the liver. The analysis of data from the literature confirms that the gut microbiota play a major role in the GVHD. Moreover, the most recent publications uncover that the lactic acid bacteria, butyrogenic bacteria and bacterial cross feeding were the missing pieces in the puzzle. This open new bacteria-based strategies in the treatment of GVHD.